Very Long–Term (10 to 14 Year) Outcomes After Percutaneous Coronary Intervention Versus Coronary Artery Bypass Grafting for Multivessel Coronary Artery Disease in the Bare-Metal Stent Era. (August 2016) - Shiomi, Hiroki; Yamaji, Kyohei; Morimoto, Takeshi; Shizuta, Satoshi; Nakatsuma, Kenji; Higami, Hirooki; Furukawa, Yutaka; Nakagawa, Yoshihisa; Kadota, Kazushige; Ando, Kenji; Sakata, Ryuzo; Okabayashi, Hitoshi; et al.
Abstract : Background—: Many of the previous randomized trials comparing percutaneous coronary intervention (PCI) with coronary artery bypass grafting (CABG) in patients with multivessel coronary artery disease reported equivalent or better survival with CABG as compared with PCI at 5-year follow-up. However, 5-year follow-up might be too short to evaluate the true differences in long-term clinical outcomes between PCI and CABG. Methods and Results—: Among 8934 patients enrolled in the extended 10- to 14-year follow-up study of the CREDO-Kyoto registry cohort-1 (Coronary Revascularization Demonstrating Outcome study in Kyoto) conducted in the bare-metal stent era, 5152 (PCI: n=3490 and CABG: n=1662) patients had multivessel coronary artery disease without left main disease. Median follow-up duration was 11.2 (interquartile range: 10.2–12.2) years. The cumulative 10-year incidence of all-cause death was not significantly different between PCI and CABG (32.2% versus 31.7%; log-rank P =0.93). After adjusting for confounders, however, the mortality risk of PCI was significantly higher than that of CABG (hazard ratio, 1.19 [95% confidence interval, 1.02–1.39]; P =0.03). Within 5 years after the index procedure, the risk for all-cause death was significantly higher after PCI than after CABG (hazard ratio, 1.41; 95% CI, 1.12–1.79; P =0.004). By a landmark analysis at 5 years, however, the cumulative 10-year incidence of and adjusted risk for all-cause death beyond 5 years were not significantly different between PCI and CABG (19.3% versus 20.0%; log-rank P =0.22 and hazard ratio, 1.02, 95% confidence interval, 0.83–1.26; P =0.82). Conclusions—: CABG as compared with PCI was associated with better 10-year survival in patients with multivessel coronary artery disease. However, the benefit of CABG compared with PCI on late mortality beyond 5 years was not observed in this study. Abstract : Supplemental Digital Content is available in the text.